Clinical Trials: Advancing Medical Solutions for Health (Asian Journal of Pharmaceutics (AJP), 2024)
A clinical trial is a study conducted on human subjects to find solutions to specific medical problems. Thebest and quickest way to uncover treatments that are effective in individuals and to improve health is throughwell-conducted clinical trials. The safety and efficacy of new treatments and applications of establishedones are evaluated in clinical trials. The focus of observational trials is on populations or large groups ofpeople experiencing health problems in their everyday environments. Clinical trials, which aim to evaluatethe efficacy of a treatment, are a highly specialized type of biological experiment. Clinical pharmacologistsconduct phase I drug kinetics, safety, and gross effects studies on human volunteers. Phase II testing involvesstudying the drug’s effects on a smaller group of patients to determine its pharmacokinetics, safety, andtherapeutic efficiency; phase III testing involves studying hundreds more patients, primarily to determine thedrug’s safety and therapeutic efficacy. If this measure passes, the medicine can officially be sold. Medicalprofessionals continue to provide feedback on the drug’s safety, side effects, and effectiveness even after ithas been commercialized.